2021
DOI: 10.1111/eth.13166
|View full text |Cite
|
Sign up to set email alerts
|

Exploration influences problem solving in the fawn‐footed mosaic‐tailed rat (Melomys cervinipes)

Abstract: The relationship between an animal's personality and its problem solving ability has become a popular topic of investigation. However, results are conflicting, suggesting that these relationships may be species-specific. We investigated these relationships in a native Australian rodent, the fawn-footed mosaic-tailed rat (Melomys cervinipes).We predicted that more exploratory and less anxious mosaic-tailed rats would be better problem solvers (e.g. faster to solve the problem) as they would interact with the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…In support of this, mosaic-tailed rats are capable innovators [ 24 ]. Previous studies have found that more exploratory mosaic-tailed rats are better problem solvers than avoidant individuals [ 25 ]. Mosaic-tailed rat personality has also been linked to some physiological measures (glucose and testosterone concentrations, [ 26 ]), suggesting a potential for adrenocortical effects on problem solving.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this, mosaic-tailed rats are capable innovators [ 24 ]. Previous studies have found that more exploratory mosaic-tailed rats are better problem solvers than avoidant individuals [ 25 ]. Mosaic-tailed rat personality has also been linked to some physiological measures (glucose and testosterone concentrations, [ 26 ]), suggesting a potential for adrenocortical effects on problem solving.…”
Section: Introductionmentioning
confidence: 99%
“…Data collection occurred between August 2018 and March 2021. Tests were conducted during the peak activity period of mosaic‐tailed rats (18:00–22:00 h; Wood, 1971 ) under red light (except for the obstruction test, see below), which does not interfere with mosaic‐tailed rat behaviors (Paulling et al, 2019 ; Rowell & Rymer, 2021a , 2021b ). To encourage animals to interact with the food‐related puzzle tests, animals were not fed on the days of these tests until after the tests were complete.…”
Section: Methodsmentioning
confidence: 99%
“…(a) Matchbox task; (b) cylinder task with food (black circle) inside and tinfoil over one end; (c) Trixie dog activity board with pillar, tile, and lever tasks; and (d) obstruction task with a piece of crumpled paper blocking the entrance. From Rowell and Rymer ( 2021a ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations